Do Self-Efficacy, Self-Regulation, and Business Capital Influence Generation Z Students' Entrepreneurial Interest in Fashion Sector? An exploratory study in Batam City - Shinta Wahyu Hati; Esty Rahayu (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Entrepreneurial interest among Generation Z is shaped by multiple individual and contextual factors. In Indonesia, MSMEs contribute 60.5% of GDP, making youth entrepreneurship—particularly in high-growth sectors such as fashion—a national policy priority. However, the relative importance of psychological and resource-based determinants remains empirically underexplored among Generation Z students in Batam City. Objective: This exploratory study examines the direct influence of self-efficacy, self-regulation, and business capital on entrepreneurial interest in the fashion sector among Generation Z students in Batam, Indonesia. Methods: A purposive sampling approach was applied to 396 students drawn from a population of 36,279 at nine universities in Batam, using the Yamane formula and proportional allocation across institutions. Respondents met three criteria: active student status, Generation Z birth cohort (born 1997–2012), and current enrollment in an entrepreneurship course. A structured Likert-scale questionnaire measured all constructs; data were analyzed using multiple linear regression (SPSS 29). Results: All three predictors exerted significant positive effects on entrepreneurial interest. Standardized coefficients: self-efficacy (β = 0.487; p < 0.001), self-regulation (β = 0.137; p = 0.004), and business capital (β = 0.118; p = 0.005). Jointly, they explained 37.3% of variance (F = 79.380; p < 0.001), with self-efficacy as the dominant predictor. Conclusion: Self-efficacy is the principal driver of Generation Z entrepreneurial interest in fashion, followed by business capital and self-regulation. These findings underscore the need for integrated university programs combining confidence-building activities, self-regulatory skill development, and capital access support to stimulate youth entrepreneurship in Batam City.